Content Vol. 41 No. 3 (2020) - Editorial, Coordinador (Revista Mexicana de Ingenieria Biomedica, 2020)
E-book edition of the volume 41, number 3, year 2020, of the Revista Mexicana de Ingeniería Biomédica. In this issue: Información general (General Information) Comité Editorial (Editorial Board) Mesa Directiva (General Board) Índice (Contents) Modified Oregonator: an Approach from the Complex Networks Theory Set of Simulators of the Electrophysiology of the A-Type Potassium Current (IA) in Neurons Probabilistic Multiple Sclerosis Lesion Detection using Superpixels and Markov Random Fields Biped Gait Analysis based on Forward Kinematics Modeling using Quaternions Algebra Electrical Cochlear Response as an Objective Measure of Hearing Threshold and Hearing Performance Evaluation in Pediatric Cochlear Implant Users